2004
DOI: 10.1107/s090744490401354x
|View full text |Cite|
|
Sign up to set email alerts
|

Two orthorhombic crystal structures of a galactose-specific lectin fromArtocarpus hirsutain complex with methyl-α-D-galactose

Abstract: Based on their carbohydrate specificity, the jacalin family of lectins can be divided into two groups: galactose-specific and mannose-specific. The former are cytoplasmic proteins, whereas the latter are localized in the storage vacuoles of cells. It has been proposed that the post-translational modification in some of the lectins that splits their polypeptide chains into two may be crucial for galactose specificity. The mannose-specific members of the family are single-chain proteins that lack the above modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
2
16
0
1
Order By: Relevance
“…Also, the symmetry in the three-dimensional structure is not refl ected in the sequence. In the meantime, the crystal structures of several other β-prism I fold plant lectins became available (Lee et al 1988;Bourne et al 1999;Bourne et al 2004;Rao et al 2004;Gallego et al 2005;Rabijns et al 2005;Yen-Chieh et al 2006). Their subunits share the basic structural and carbohydrate-binding characteristics of jacalin and artocarpin.…”
Section: Introductionmentioning
confidence: 97%
“…Also, the symmetry in the three-dimensional structure is not refl ected in the sequence. In the meantime, the crystal structures of several other β-prism I fold plant lectins became available (Lee et al 1988;Bourne et al 1999;Bourne et al 2004;Rao et al 2004;Gallego et al 2005;Rabijns et al 2005;Yen-Chieh et al 2006). Their subunits share the basic structural and carbohydrate-binding characteristics of jacalin and artocarpin.…”
Section: Introductionmentioning
confidence: 97%
“…Crystallographic studies of gJRLs have showed that the sugar binding sites contain three loops (residues 46-52, 76-82, and 122-125) and Gly, the N-terminus of α-chain. 41,43,53,54) The primary binding site of gJRLs could accommodate galactose and N-acetylgalactosamine residues. Notwithstanding TAA-G contained four residues common in the primary site of other gJRLs, Gly1, Tyr122, Trp123, and Asp125, TAA-G could not recognize T-antigen and a few α-glycosides of GalNAc.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al 47) reported the contents of two types of JRLs in seeds of two Artocarpus species, and Van Damme et al 9) reported them in bark and seeds of M. nigra. Notes: TAA-G sequence is aligned using CLUSTAL W with other gJRLs, AHL: Artocarpus hirsuta lectin, 41) Frutalin, 42) Jacalin, 43) MPA, 43) Morniga G. 9) Shaded letters denote the residues found in the binding with T-antigen. [44][45][46] Asterisks indicate identical residues, and dashes or colons, similar residues.…”
Section: Sugar-binding Specificity Of Taasmentioning
confidence: 99%
“…The family contains a variety of compounds, which showed cytotoxicity and antimicrobial (Rocha et al 2007;Kuete et al 2007). Many triterpenoids such as ursolic and oleanolic acids from the methanolic extract of Pourouma guianensis leaves inhibited the growth of Leishmania amazonensis (Santos et al 2004); stilbenes from the aerial parts of Artocarpus integer showed antimalarial activity (Boonlaksiri et al 2000); lectin from Artocarpus hirsuta observed insecticidal activity (Rao et al 2004); three polyphenolicrich fractions were obtained from the chloroform stem bark extracts of Streblus asper possessed insecticidal activity against the fifth-instar of Dysdercus cingulatus (Hashim and Devi 2003). The crude aqueous extract of the stem bark of S. asper revealed significant macrofilaricidal activity against Litomosoides carinii and Brugia malayi in rodents (Rastogi et al 2006) and the ethanol extract of stem bark of Naucleopsis glabra exhibited the strongest activity against Gram-positive bacteria (Kloucek et al 2007).…”
Section: Introductionmentioning
confidence: 98%